Building condition survey and assessment report: The use and benefits in sub-sale housing property valuation - Mustafa, N.K.F.; Alias, A.; Ismail, N.A.; Che-Ani, A.I. (2010)
The levels of defects and deteriorations in a building are the great influence to indicate the building performance instead of the service systems provided. The interaction for both people and surroundings towards the life cycle of a building gives impact on the property values. Dealing with the sub-sale housing properties, it require for Valuers expertise, experience and knowledge in property Valuation in which the fourteen procedures of conducting inspection and referencing of the property were highlighted in Malaysian valuation Standard. It is understand that the scope of inspection· is limited for the purpose of valuation only. Due to integration of skill and knowledge,the condition survey and assessment of building is foreseeable to help the Valuers in preparing an accurate valuation for sub-sale houses. Questionnaire survey forms were distributed among Valuers from various public and private sectors to discover the professional perspective on this approach. The paper is of value in assessing the use and benefits of Building Condition Survey and Assessment (BCSA) report in sub-sale housing property valuation and showing that it can be used to estimate the potential value of the respective property. The main finding shows that while the Valuers acknowledge the importance of having BCSA, it is not really put into practice in conducting the sub-sale housing property valuation.